Open-Path Atmospheric Transmission of Diode-Pumped Alkali Lasers in Maritime and Desert Environments. Issue 4 (April 2023) - Rice, Christopher A.; Pitz, Greg A.; Guy, Matthew R.; Perram, Glen P.
A tunable diode laser absorption spectroscopy (TDLAS) device has been developed to study long-path atmospheric transmission near diode pumped alkali laser (DPAL) emission wavelengths. By employing a single aperture and retro reflector in a mono-static configuration, the noise associated with atmospheric and platform jitter were reduced by a factor of ∼30 and the open-air path length was extended to 4.4 km and over a very broad spectral range, up to 120 cm −1 . Water vapor absorption lines near the rubidium (Rb) and cesium (Cs) variants of the DPAL near 795 and 894 nm, oxygen lines near the potassium (K) DPAL near 770 nm, and water vapor absorption in the vicinity of the neodymium-doped yttrium aluminum garnet (Nd:YAG) laser 1.064 μm and chemical oxygen iodine laser (COIL) 1.3 μm lines were studied. The detection limit for path absorbance increases from ΔA = 0.0017 at 100 m path length to 0.085 for the 4.4 km path. Comparison with meteorological instruments for maritime and desert environments yields agreement for the 2.032 km path to within 1.5% for temperature, 4.5% for pressure, and 5.1% for concentration, while agreements for the 4.4 km path are within 1.4% for temperature, 7.7% for pressure, and 23.5% for concentration. An intra cavity output spectroscopy (ICOS) device was also used as a spectral reference to verify location of atmospheric lines. Implications of TDLAS collection system design on signal-to-noise (S/N) are discussed as well as the effect of path turbulence on baseline noise and inform the selection of the DPAL variant least affected by molecular absorption. Graphical Abstract This is a visual representation of the abstract.